2015
DOI: 10.1039/c4ta05923a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the performance of dye-sensitized solar cells: doping SnO2photoanodes with Al to simultaneously improve conduction band and electron lifetime

Abstract: ARTICLE This journal isAmong the semiconductor materials used in dye-sensitized solar cells (DSSCs), SnO 2 is an important alternative material to TiO 2 used in photoanode. In this work, SnO 2 and Al-doped SnO 2 nanocrystals were prepared via a simple hydrothermal method, and we found both key dual-factors, such as tuning the conduction band and suppressing the charge recombination, are synchronously improved in the Al-doped samples for the first time. The electron lifetime is significantly improved and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Researches were carried out on doped SnO 2 using variable metals such as Zn, 37,66 Al, 67,68 and Ga. 69 69 who found that the highest efficiency of about 7.11% could be obtained after the post treatment with TiCl 4, which is greater than their own previous work. 67 Finally, it became apparent that SnO 2 by the same token of TiO 2 shows enhanced PCE by the tuning of bandgap and reducing the charge recombination. As moving through the papers based on doping on SnO 2 photoanodes, some common features were observed such as (a) hydrothermal method was commonly used for the synthesize of all the doped SnO 2 materials and (b) they blocks the interfacial charge recombination as well as shows a negative shift to the CB of SnO 2 .…”
Section: Metal Oxide Based Photoanodesmentioning
confidence: 88%
See 1 more Smart Citation
“…Researches were carried out on doped SnO 2 using variable metals such as Zn, 37,66 Al, 67,68 and Ga. 69 69 who found that the highest efficiency of about 7.11% could be obtained after the post treatment with TiCl 4, which is greater than their own previous work. 67 Finally, it became apparent that SnO 2 by the same token of TiO 2 shows enhanced PCE by the tuning of bandgap and reducing the charge recombination. As moving through the papers based on doping on SnO 2 photoanodes, some common features were observed such as (a) hydrothermal method was commonly used for the synthesize of all the doped SnO 2 materials and (b) they blocks the interfacial charge recombination as well as shows a negative shift to the CB of SnO 2 .…”
Section: Metal Oxide Based Photoanodesmentioning
confidence: 88%
“…In contrast to doped TiO 2 photoanodes, doped ZnO and SnO 2 photoanodes are very rare. Researches were carried out on doped SnO 2 using variable metals such as Zn, 37,66 Al, 67,68 and Ga 69 . Both Dou et al and Li et al have investigated the effect of Zn doping in SnO 2 photoanodes.…”
Section: Revamping Of Photoanodementioning
confidence: 99%
“…It is an efficient way to inhibit these back reactions by doping SnO 2 with other metal elements. Duan et al doped SnO 2 nanoparticle with Al and found the tuning of the conduction band and suppression of charge recombination [6]. Li et al…”
Section: Introductionmentioning
confidence: 99%
“…The wider bandgap of SnO 2 , compared to anatase TiO 2 (3.2 eV) creates fewer oxidative holes in the valence band under UV illumination, so as to minimize dye degradation rate and long term stability of DSSCs 16 17 . Because of these appealing properties, SnO 2 has been recently utilized in other advanced applications 18 19 20 , including hydrogen gas sensing 21 22 . Various synthesis techniques of SnO 2 nanocomposites have also been reported in recent literature 23 24 .…”
mentioning
confidence: 99%